Attention-deficit hyperactive disorder (ADHD) presenting with major depression in an adolescent: a case report - Noor Azimah Muhammad; Noor Mikraz MI; Wan Salwina WI (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Major depressive disorder is an important psychiatric illness that can be a life-threatening condition when it presents with suicidality. This case report describes an adolescent who presented with major depressive disorder but with an underlying undiagnosed attention deficit hyperactive disorder (ADHD). The 17-year-old male adolescent presented with psychosomatic complaint of non-resolving left sided chest pain. He also had major depressive symptoms and suicidal ideation. His ADHD was being missed. This case highlights the difficulty of diagnosing ADHD during adolescence as the presentation may not be as typical as during early-childhood years.